Penguatan Tata Kelola Administrasi Rumah Sakit Melalui Inovasi Manajemen Dan Kepemimpinan Berorientasi Pasien: Strengthening Hospital Administrative Governance Through Management Innovation and Patient-Oriented Leadership - Ayuningtias, Aulia Dini; Ginting, Rian Fedriko; Mungkur, Naik Parsaulian; Wulandari, Putri (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Hospital administrative governance plays a crucial role in determining service quality and patient experience. However, in practice, hospitals frequently encounter challenges such as inefficient service workflows, prolonged waiting times, and weak coordination among administrative units. These issues negatively affect patient satisfaction and overall hospital performance. Therefore, this Community Service activity aimed to strengthen hospital administrative governance through management innovation and the application of patient-oriented leadership principles. This activity employed a descriptive qualitative approach using educational sessions, training, and Focus Group Discussions (FGD). The target population consisted of administrative staff and heads of administrative units at Mitra Sejati General Hospital, Medan, North Sumatra, with a total sampling of 20–30 participants. The variables assessed included knowledge of hospital administrative governance, efficiency of administrative service workflows, and patient-centered leadership orientation. Data were collected using pre-test and post-test questionnaires, observation checklists, and structured discussion guides, and were analyzed descriptively using frequency distributions, percentages, and narrative analysis. The results demonstrated an improvement in participants’ knowledge and understanding of patient-oriented hospital administrative governance. Post-test scores increased compared to pre-test scores across all assessed aspects, particularly in administrative workflow efficiency and leadership roles in supporting patient-centered services. Qualitative findings indicated that participants were able to identify administrative problems within their respective units and formulate recommendations for improving service workflows and developing simplified standard operating procedures. Based on these findings, this Community Service activity was effective in enhancing the capacity of hospital administrative personnel to implement efficient and patient-centered administrative governance. It is recommended that the outcomes of this activity be integrated into internal hospital policies and standard operating procedures, supported by continuous mentoring to ensure sustainable improvements in service quality and patient satisfaction.